Past, present and future in the geographical distribution of Mexican Tepezmaite cycads: Genus Ceratozamia - Gómez-Díaz, Jorge Antonio; Carvajal-Hernández, César Isidro; Dáttilo, Wesley (PloS one, 2024)
Ceratozamia morettii , C . brevifrons , and C . tenuis are cycads considered endangered in montane forests in the center of Veracruz state. However, the amount of theoretical and empirical information available on the historical distribution of these species and how they could be affected in the future by the effects of climate change still needs to be increased. Our objective was to generate information on the spatial distribution of the species since the last glacial maximum, present, and future. To map the spatial distribution of species, we created a potential distribution model for each species. The spatial data used for the models included 19 bioclimatic data variables in the present, at the last glacial maximum using two models (CCSM4 and MIROC), and in the future (2080) using two models of the RCP 8.5 scenario of climate change (HadGEM2-CC and MIROC5). We found that each species occupies a unique ecoregion and climatic niche. Ceratozamia morettii and C . tenuis have a similar pattern with an expansion of their distribution area since the last glacial maximum with a larger distribution area in the present and a projected reduction in their distribution under future climatic conditions. For C . brevifrons , we also showed an increase in their distributional area since the last glacial maximum. We also showed that this expansion will continue under future climatic conditions when the species reaches its maximum distributional area. Projections about the future of these endemic cycad species show changes in their habitat, highlighting that temperate zone species ( C . morettii and C . tenuis ) will face imminent extinction if no effort is made to protect them. On the other hand, the tropical climate species ( C . brevifrons ) will be favored.